BIOLOGICAL DIVERSITY OF MYRIAPOD COMMUNITIES (DIPLOPODA, CHILOPODA) ON THE MADARA PLATEAU, NORTH-EASTERN BULGARIA: BIOLOGICAL DIVERSITY OF MYRIAPOD COMMUNITIES (DIPLOPODA, CHILOPODA) ON THE MADARA PLATEAU, NORTH-EASTERN BULGARIA - Bachvarova, Darina; Doichinov, Aleksandar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The assessment of the biodiversity of natural complexes has a significant practical application and can be used as a sample for the analysis of the role of environment in the spread and bio-geographic distribution of species, the models of faunogenesis and the establishment of the specific biota. The aim of this research is to study the α- and β-diversity of millipede and centipede communities in the various habitats along the Madara Plateau, North-eastern Bulgaria. The material for the analysis was collected through pitfall traps, arranged in lines of ten on eleven sampling plots, which have been reported on a monthly basis in the period June 2012 - February 2015. A total of 3415 myriapods have been collected – 2776 millipedes of 12 species and 639 centipedes of 16 species. The millipede communities feature higher diversity in species and a comparatively higher degree of equality compared to those of the centipede communities. The forest habitats along the Madara Plateau are characterized with high diversity of millipede communities, while the open areas are the preferred habitat of Chilopoda.